Projected Rapid Habitat Expansion of Tropical Seagrass Species in the Mediterranean Sea as Climate Change Progresses - Beca-Carretero, Pedro; Teichberg, Mirta; Winters, Gidon; Procaccini, Gabriele; Reuter, Hauke (Frontiers in Plant Science, 2020)
During the last 150 years, the tropical seagrass species Halophila stipulacea has established itself in the southern and eastern parts of the Mediterranean Sea. More recently (2018), Halophila decipiens was observed for the first time in the eastern Mediterranean and was described as the second non-native seagrass species in the Mediterranean Sea. We implemented a species distribution model (SDM) approach to 1) hindcast the habitat suitability of H. stipulacea over the last 100 years in the Mediterranean basin, and 2) to model the increase in the potential habitat suitability of H. stipulacea and H. decipiens during the current century under two very different climate scenarios, RCP 2.6 (lowest carbon emission scenario) and RCP 8.5 (highest carbon emission scenario). In addition, a principal component analysis (PCA) and k-means cluster based on temperature and salinity drivers were applied to visualize the distance and relatedness between the native and invasive H. stipulacea and H. decipiens populations. Results from this PCA suggest that the H. stipulacea populations of the Mediterranean and Red Sea are likely to be similar. In contrast, H. decipiens from the Mediterranean is more related to the Atlantic populations rather than to the Red Sea populations. The hindcast model suggests that the expansion of H. stipulacea was related to the increases in seawater temperatures over the last 100 years. The SDMs predict that more suitable habitats will become available for both tropical species during this century. The habitat suitability for H. stipulacea will keep expanding westwards and northwards as the Mediterranean continues to become saltier and warmer. . In comparison, the SDMs built for H. decipiens forecasts a restricted habitat suitability in the south-eastern Mediterranean Sea at the present environmental conditions and predicts a progressive expansion with a potential increase in habitat suitability along 85% of the Mediterranean coastline. The rapid expansion of non-native seagrass species could alter the Mediterranean’s seagrass community and may entail massive impacts on associated ecosystem functions and services, impacts that have severe socio-economic consequences.